Influencia de dos medios de cultivo en la productividad de tres cultivares de coliflor (Brassica Oleracea, L) de colores (Sunset, Verde Trevi Y Graffiti), bajo condiciones orgánicas de cultivo a 3.384 M.S.N.M. Otón – Pichincha 2012 - Salcedo Criollo, Orlando Bladimir (2014)
This research developed in the canton Cayambe, parish Otón, in the legal community Chaupiestancia, was carried out with the purpose of determining the influence of two culture media in the productivity of three cultivars of cauliflower of colors, (Sunset, Green Fountain and Graffiti), with the aim of improving the production and give an alternative crop to farmers and the final consumer. For this purpose we used a factorial experimental design DCA A x B with eight treatments and four replications, in an area of 480 m2 with a total of 32 experimental units, each of which consisted of 35 seedlings in 15 m2 and the net plot consisted of 15 seedlings for the two culture media. The variables evaluated were: the germination percentage, number of leaves, width of leaves, long leaves, size of Pella, weight of Pella, compaction and performance.